Project-based Module Development as Teaching Material for Light Vehicle Engine Maintenance: Validity Test - Muslim, Muslim; Jalinus, Nizwardi; Refdinal, Refdinal; Arif, Ahmad; Wagino, Wagino (JINoP (Jurnal Inovasi Pembelajaran), 2023)
The limitations of teaching materials are not equipped with motivating content and inappropriate learning strategies, which make students feel difficult in mastering the competencies they need. The purpose of this present study is to test the level of validity of the product developed in the form of a learning module. The development procedure used is the ADDIE model. Research data was obtained through observation, interviews, and research questionnaires. The research questionnaire is used to obtain the validity value of the product being developed. The validity test was carried out in the development phase, for this reason, this research stage describes only the development phase. Validity test data was obtained by distributing questionnaires to 5 expert validators consisting of 2 expert lecturers and 3 productive teachers. The results of the study show that teaching materials developed on a project basis have a valid category. Product development will continue with revisions provided by a team of experts. The steps to be taken after the validation stage are the practicality and effectiveness of the product being developed. Teachers can also develop and arrange teaching materials so that the use of this product is not limited to the competencies that are developed. There is a need for further research regarding the development of teaching materials to create teaching materials that can motivate students in learning.